THE EFFECT OFGOOD CORPORATE GOVERNANCE AND OWNERSHIP STRUCTURE ON FINANCIAL PERFORMANCE - Ni Nyoman Ayu Suryandari; AA Putu Gede Bagus Arie Susandya (Jurnal Ekonomi, 2023)
This study aims to determine the effect of good corporate governance and ownership structure on financial performance in property and real estate companies for the 2018-2021 period. The population in this study are all property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The samples in this study were 80 property and real estate companies. Determination of the sample using purposive sampling method. The analysis technique used is multiple linear regression analysis. The results of this study indicate that the independent board of commissioners variable has a negative effect on financial performance. The board of directors variable has a positive effect on financial performance. The audit committee variable has a negative effect on financial performance. Managerial ownership and institutional ownership variables have no effect on financial performance.